Manifestaciones orales en pacientes con covid-19 - Toapanta Torres, Sofia De Los Ángeles (2025)
Introduction: It is important to understand the various oral manifestations that may appear in a patient who has tested positive for COVID-19. The coronavirus represents a significant global health risk due to its rapid spread and ease of transmission. This virus spreads through direct transmission or physical contact. In the symptomatic phase, the patient may present with cough, fever, loss of taste, myalgia, and even severe respiratory failure. Objective: To conduct an in-depth analysis of the oral manifestations that may occur because of COVID-19. Materials and Methods: The methodological strategy was primarily based on an extensive literature review using the PICO format. From the problem statement analysis, an initial consultation of 546 articles was conducted. After a selection and filtering process, 14 key studies were chosen for review and detailed analysis to identify and compile the most relevant studies related to the research topic. Results: According to the findings obtained, it is essential to understand the oral manifestations present in these patients to provide appropriate dental treatment. Knowing the various manifestations that may occur in these patients is crucial, as it can present a challenge for dentists. Conclusion: It is essential for dentists to have the necessary and adequate training to identify the needs of patients who have had COVID-19. Studies have shown that patients infected with COVID-19 may develop various oral manifestations because of the virus, including aphthous ulcers, herpetiform lesions, or candidiasis.